2016
DOI: 10.1088/0031-9155/61/6/2514
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach to the accurate prediction of multi-leaf collimator positional errors

Abstract: Discrepancies between planned and delivered movements of multi-leaf collimators (MLCs) are an important source of errors in dose distributions during radiotherapy. In this work we used machine learning techniques to train models to predict these discrepancies, assessed the accuracy of the model predictions, and examined the impact these errors have on quality assurance (QA) procedures and dosimetry. Predictive leaf motion parameters for the models were calculated from the plan files, such as leaf position and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 30 publications
2
98
1
Order By: Relevance
“…In addition, we implemented a machine learning model. Several prior studies have reported that machine learning models, using information from TPS, were useful for prediction of various factors . In this study, we also implemented a machine learning‐based linear regression model to predict GPR.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we implemented a machine learning model. Several prior studies have reported that machine learning models, using information from TPS, were useful for prediction of various factors . In this study, we also implemented a machine learning‐based linear regression model to predict GPR.…”
Section: Methodsmentioning
confidence: 99%
“…In pathognomy, several studies have addressed the prediction of clinical outcome of stereotactic body radiation therapy for lung cancer using radiomic features based on CT images . In medical physics, Carlson et al reported the prediction of multi‐leaf collimator positional errors using machine learning . Sum et al reported the prediction of beam output and derived MUs using machine learning .…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is a subfield of data science that focuses on designing algorithms that can learn from and make predictions on data. Machine learning applications in radiotherapy have emerged increasingly in recent years, with applications including predictive modeling of treatment outcome in radiation oncology,1, 2, 3, 4, 5, 6, 7 treatment optimization,8, 9, 10, 11 error detection and prevention,12, 13, 14, 15 and treatment machine quality assurance (QA) 16, 17, 18, 19. These machine learning techniques have provided physicians and physicists information for more effective and accurate treatment delivery as well as the ability to achieve personalized treatment.…”
Section: Introductionmentioning
confidence: 99%